2007
DOI: 10.1186/1476-4598-6-31
|View full text |Cite
|
Sign up to set email alerts
|

LEDGF/p75 has increased expression in blasts from chemotherapy-resistant human acute myelogenic leukemia patients and protects leukemia cells from apoptosis in vitro

Abstract: Background: Relapse due to chemoresistant residual disease is a major cause of death in acute myelogenous leukemia (AML). The present study was undertaken to elucidate the molecular mechanisms of chemoresistance by comparing differential gene expression in blasts from patients with resistant relapsing AML and chemosensitive AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 34 publications
6
75
2
1
Order By: Relevance
“…LEDGF/p75 is a potent oncogene with known diverse functions in cell survival, chemotherapy resistance, tumor progression (41,48,49), and leukemic transformation via interactions with MLL oncoproteins (30). Although our studies indicated a tight convergence of LEDGF/p75 and JPO2 on promigratory AKT signaling, we observed that JPO2 and LEDGF/p75 did not always have overlapping cellular and signaling effects in UW228 and UW426 medulloblastoma cell lines.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…LEDGF/p75 is a potent oncogene with known diverse functions in cell survival, chemotherapy resistance, tumor progression (41,48,49), and leukemic transformation via interactions with MLL oncoproteins (30). Although our studies indicated a tight convergence of LEDGF/p75 and JPO2 on promigratory AKT signaling, we observed that JPO2 and LEDGF/p75 did not always have overlapping cellular and signaling effects in UW228 and UW426 medulloblastoma cell lines.…”
Section: Discussioncontrasting
confidence: 41%
“…Future studies to determine how JPO2 and the PI3K/AKT pathway act convergently or independently to mediate EMT and migratory/metastatic medulloblastoma phenotypes would clearly be of therapeutic interest. We observed that JPO2 binds to LEDGF/p75, a known oncoprotein highly expressed in multiple cancer types (31,40,41), that is also coordinately upregulated with JPO2 in medulloblastoma. Our data, which is the first to implicate LEDGF/p75 in medulloblastoma suggest LEDGF/p75 and JPO2 may act via a common transcriptional signaling complex to promote Myc:PI3K/AKTassociated medulloblastoma transformation.…”
Section: Discussionmentioning
confidence: 86%
“…Comprehensive gene analysis on a microarray in cervical carcinoma cells (squamous cell carcinoma) showed that MT-CO1 was increased by a factor greater than two in RRCs compared with radiosensitive cells (15). Also, in human acute myelogenic leukemia cells, MT-CO3 was upregulated in chemoresistant cells compared with in chemosensitive cells (16). However, these study did not verify that overexpression of MT-CO1 actually induces radioresistance.…”
Section: Discussioncontrasting
confidence: 42%
“…The relationship between cytochrome c oxidase and chemo or radioresistance has been reported in various tumor cell lines (15)(16)(17)(18)(19). Comprehensive gene analysis on a microarray in cervical carcinoma cells (squamous cell carcinoma) showed that MT-CO1 was increased by a factor greater than two in RRCs compared with radiosensitive cells (15).…”
Section: Discussionmentioning
confidence: 99%
“…In −/− mouse embryonic fibroblasts (MEFs) fewer genes were up-or down-regulated (< 200) and, again, a particular transcriptional network was not identified [101]. Studies focused on other biological questions have implicated p75 in modulating apoptosis and other cellular responses to stress and have suggested a role as an auto-antigen in certain disease states [66][67][68][70][71][72]84,107]. However, p75 depletion does not disproportionately alter stress-responsive gene transcription, nor does HIV appear to preferentially target such genes [85,101,110].…”
Section: P75: Identification and Putative Cellular Function Of A Lentmentioning
confidence: 99%